Mapping modern Mahayana: Chinese Buddhism and migration in the age of global modernity - Reinke, Jens (Dialectics of the global, 2021)
Frontmatter -- On the Series -- Contents -- Acknowledgements -- Abstract -- Mapping Modern Mahayana -- The Many Transnationalisms of Renjian Buddhism -- Migrating Bodhisattvas and Fo Guang Shan Religious Mobility -- Chineseness Globalized -- Generating Global Pure Lands -- Purifying the Multitude -- Fo Guang Shan and Global China as a Spatial Order -- List of Abbreviations -- List of Figures -- Bibliography -- Index